PROLIFERATION OF INNOVATION ON FINANCE MARKET: THEORETICAL ASPECT - David I. Philippov (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The present day understanding of innovation and innovation activity has a long history. Innovation plays a key role in efficient functioning of finance market and economic growth. At the same time industry of finance services is an appealing field for scientific observations. Companies, which provide finance services, as a rule have not got protection of intellectual property in their innovation activity. However, the absence of these rights has not eliminated incentives or possibilities to introduce innovation by companies. The article shows that value innovation accentuates equally on value and innovation for customers, clients and the company. This concept aims at developing strategy of growth, new products and services (over-configuration of existing products and services) that are valuable for the client.